1997
DOI: 10.1002/(sici)1520-670x(1997)10:4<249::aid-jtra6>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary zinc and copper on ?-Amyloid precursor protein expression in the rat brain

Abstract: The β‐amyloid precursor protein (APP) is the source of the amyloid β‐peptide that accumulates in the brain in Alzheimer's disease. Recently, APP has been shown to bind zinc and copper, and this binding has been suggested to control APP conformation and stability. In vitro studies show that zinc ions cause β‐amyloid protein to form plaques resembling the amyloid plaques found in the brains of patients with Alzheimer's disease. This suggests a role for zinc and/or copper in the neuropathogenesis of Alzheimer's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(45 reference statements)
2
3
1
Order By: Relevance
“…The high Zn diet of Davis (1997) also resulted in a trend towards decreased brain Cu levels, as was found in this study. The antagonistic affect of Zn on Cu levels is well known, and appears to be mediated primarily by competition for uptake at the level of the intestinal mucosa (Fischer et al 1984).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high Zn diet of Davis (1997) also resulted in a trend towards decreased brain Cu levels, as was found in this study. The antagonistic affect of Zn on Cu levels is well known, and appears to be mediated primarily by competition for uptake at the level of the intestinal mucosa (Fischer et al 1984).…”
Section: Discussionsupporting
confidence: 86%
“…Previous metal feeding studies using rats have demonstrated increased brain Cu levels (11%) as a result of a high Cu diet, and increased brain Zn levels (13%) as a result of a high Zn diet (Davis 1997). The high Zn diet of Davis (1997) also resulted in a trend towards decreased brain Cu levels, as was found in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Panemangalore and Bebe reported that EC SOD was decreased only in copper deficiency (<1 g/g) or in rats fed copper marginal diets (approximately 2 g/g) containing high zinc concentrations (>60 g/g) [22]. Davis showed that there was no difference in EC SOD in rats fed low dietary zinc (5 g/g) when comparing groups fed 3 g copper/g to groups fed 1.5 g/g [23]. However, EC SOD was decreased in rats fed high-zinc diets low in copper [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Finding no copper effect on EC SOD was not surprising. Panemangalore and Bebe [22] and Davis [23] showed zinc status and the degree of copper deprivation markedly affects EC SOD. Panemangalore and Bebe reported that EC SOD was decreased only in copper deficiency (<1 g/g) or in rats fed copper marginal diets (approximately 2 g/g) containing high zinc concentrations (>60 g/g) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic factors of interest would be expression of genes like the APP encoding for beta amyloids. Disturbed metabolism of metals, e.g., zinc and copper have been related to Alzheimer's disease [Davis, 1997] including decreased growth inhibitor factor (GIF) in astrocytes. GIF is recognized as metallothionein III (MT), a mainly zinc containing MT [Nordberg, 1998].…”
Section: Discussionmentioning
confidence: 99%